Kepemimpinan Transformasional di Era Postmodern: Strategi Meningkatkan Keterlibatan Spiritualitas Pemuda Gereja Karismatik - Yudhy Sanjaya; Victor Angsono Huatama; Ronald Sianipar (Sekolah Tinggi Teologi Real Batam, 2025)
This study examines the influence of Transformational Leadership on the spiritual engagement of young people in charismatic churches. The background of this study is based on the need for charismatic churches to increase the engagement of young people which has tended to decline in recent years. Transformational Leadership, which emphasizes inspiration, emotional attachment, and individual development, is believed to be able to create strong bonds that support sustainable spiritual engagement. The formulation of the research problem focuses on how Transformational Leadership can influence the engagement of young people, the strategies adopted by charismatic churches to achieve this engagement, and the challenges that arise in its implementation. This study uses a descriptive qualitative method with a literature study approach that includes journals and academic books in the last five years. A literature review was conducted to understand the relevant trends, strategies, and dynamics related to transformational leadership styles in the church. The results of the study indicate that Transformational Leadership is able to increase the engagement of young people through an inspirational approach and supporting programs such as mentoring and social service activities. The main challenges faced are adaptation to technology and the values of the younger generation. In conclusion, Transformational Leadership plays a significant role in building spiritual attachment in charismatic churches and needs to be adapted innovatively to remain relevant to the younger generation. Abstrak Penelitian ini mengkaji pengaruh Kepemimpinan transformasional terhadap keterlibatan spiritual generasi muda di gereja-gereja karismatik. Latar belakang penelitian ini didasarkan pada kebutuhan gereja karismatik untuk meningkatkan keterlibatan generasi muda yang cenderung menurun dalam beberapa tahun terakhir. Kepemimpinan transformational, yang menekankan inspirasi, keterikatan emosional, dan pengembangan individu, diyakini mampu menciptakan ikatan kuat yang mendukung keterlibatan spiritual berkelanjutan. Rumusan masalah penelitian ini berfokus pada bagaimana Kepemimpinan transformasionaldapat memengaruhi keterlibatan generasi muda, strategi yang diadopsi gereja karismatik untuk mencapai keterlibatan ini, dan tantangan yang muncul dalam implementasinya. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi literatur yang mencakup jurnal dan buku akademik lima tahun terakhir. Tinjauan literatur dilakukan untuk memahami tren, strategi, dan dinamika yang relevan terkait gaya kepemimpinan transformasional di gereja. Hasil penelitian menunjukkan bahwa Kepemimpinan transformasional mampu meningkatkan keterlibatan generasi muda melalui pendekatan inspiratif dan program-program pendukung seperti mentoring dan kegiatan pelayanan sosial. Tantangan utama yang dihadapi adalah adaptasi terhadap teknologi dan nilai-nilai generasi muda. Kesimpulannya, kepemimpinan transformasional berperan signifikan dalam membangun keterikatan spiritual di gereja karismatik dan perlu diadaptasi secara inovatif agar tetap relevan bagi generasi muda.